Pengaruh Capital Structure dan Net Profit Margin Terhadap Nilai Perusahaan Pada Perusahaan Sektor Transportasi dan Logistik Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021 - Revika Oktavia; Wahyu Indah Mursalini; Afni Yeni (Jurnal Riset dan Inovasi Manajemen, 2023)
This study aims to analyze the effect of capital structure and net profit margin on company value in transportation and logistics sub-sector companies with a sample of 21 companies listed on the Indonesian stock exchange using the purposive sampling method and based on the 2018-2021 sampling criteria. Based on the results of statistical analysis, it can be concluded that capital structure has a significant effect on the firm value of the transportation and logistics sector studied. this is proven by using the t test with a significant value of 0.003 > 0.05 and tcount 3.040 > ttable 1.989. so it can be concluded that capital structure has a significant effect on value based on statistical analysis it can be concluded that the net profit margin has no effect on the value of the companies in the transportation and logistics sector being studied. this is proven by using the t test with a significant value of 0.205 > 0.10 and tcount 1.277 < ttable 1.989. conclude that net profit margin has no effect on company value. it can be concluded that capital structure and net profit margin have a significant effect on company value in transportation and logistics sector companies listed on the Indonesia Stock Exchange in 2018-2021, with Fcount is 5.272 > Ftable 3, 11 significant value of 0.007 is smaller than the targeted significant level of 0.05. R Square of 0.115. This means that there is a contribution of 11.5% from the independent variables, namely capital structure (X1) and net profit margin (X2) to firm value (Y). While the remaining 88.5% is contributed or influenced by other variables.